University students' barriers to managing mental health during the COVID-19 pandemic: A qualitative exploration - F. A. Nurdiyanto; Irene Miracle Philian Goszal; Enggar Putri Harjanti (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
The COVID-19 pandemic and its mitigation efforts are associated with increased student mental health problems such as anxiety, stress, isolation, and lack of motivation. When left untreated, these conditions could affect students' well-being, academic achievement, social relations, and quality of life. This study aimed to explore university students' barriers to managing mental health during the COVID-19 pandemic using an explorative qualitative approach. A total of 310 students from various regions in Indonesia were recruited by purposive sampling. Data was collected by distributing qualitative questionnaires through a Google form containing informed consent, demographic data, and open-ended questions. Thematic analysis was applied to identify the patterns of the meaning of students' barriers. The barriers experienced by students in managing mental health during the pandemic are a lack of support from their closest people, restricted mobility, stigmatization, and individual characteristics. The results show support from family and closest friends is essential for managing students' mental health, especially when there is limited access to mobility and social interaction. Additionally, adaptability and disclosure are also seen to be crucial for students in managing their mental health. This study suggests a campaign for mental health literacy and providing accessible mental health services for students in crisis.